In Vitro Antimicrobial Susceptibility of Staphylococcus pseudintermedius Isolates of Human and Animal Origin - Humphries, Romney M. (J Clin Microbiol, 2016)
MIC results for 115 Staphylococcus intermedius group isolates are presented. Of these, 33% were methicillin resistant, among which 51.4% were susceptible to doxycycline, 29.7% to clindamycin, and 21.6% to trimethoprim-sulfamethoxazole. All of the isolates were susceptible to ceftaroline, daptomycin, linezolid, nitrofurantoin, quinupristin-dalfopristin, rifampin, tigecycline, and vancomycin. Of all the isolates, 82.6%, 67.8%, and 23.5% were susceptible to ciprofloxacin, erythromycin, and penicillin, respectively. No isolates harbored mupA or qacA/B genes, which suggested a lack of resistance to mupirocin or chlorhexidine.